[PP.18.28] IMPACT OF BODY MASS INDEX ON RISK FACTORS AND TARGET ORGAN DAMAGE. (September 2017) - Kyriazis, I.; Kallistratos, M.S.; Poulimenos, L.E.; Groutsis, A.; Kouremenos, N.; Koukouzeli, A.; Tsinivizov, P.; Kontogiannis, N.; Kifnidis, K.; Pagoni, S.; Koutsaki, M.; Hamodraka, E.F.; et al.
Abstract : Objective: To differentiate the sub-clinical impact of body mass index on risk factors, target organ damage, including cardiac adaptations, especially beyond hypertension. Design and method: In this observational study with a cross-sectional design, 187 patients referred or self-referred to our outpatient institution were prospectively enrolled. In all patients, medical history and physical examination as well as routine biochemical exams, clinic and 24-h blood pressure (BP) evaluation and finally echocardiography was performed. Results: Patients enrolled were mainly females (55%) aged 51, 21 ± 11 years. 38% of the patients were obese while 31% overweight. Body mass index (BMI) was highly related to office and 24-hours blood pressure levels, lipidemic and glucose profile, but not with central BP levels, pulse wave velocity (PWV) and renal function. More precisely, overweight, obese but also underweight patients had increased mean 24 hours systolic and diastolic BP levels in comparison to normal weight patients (123/75 mmHg, 125/76 mmHg, 128/72 mmHg vs 117/70 mmHg (p < 0.001), higher morning and evening 24 hours mean BP levels (p < 0.001), higher office diastolic BP levels (p < 0.001) without any significant difference in office systolic BP levels, central BP and PWV levels (p = ns). As expected, glucose as well as lipidemic profile was highly related to BMI since the higher the BMI the higher the levels of glucose, LDL abd triglycerides (p < 0.001). Conclusions: Obese overweight but also underweight patients presents increased cardiovascular risk factors and seems that a J type curve is present.